EVALUATION OF GREENHOUSE GAS EMISSIONS FROM SOLID WASTE MANAGEMENT PRACTICES IN STATE CAPITALS OF NORTH EASTERN NIGERIA - MSHELIA RICHARD BALTHI (Journal of Engineering Studies and Research)
Greenhouse gas (GHG) emissions due to solid waste management (SWM) techniques being practiced in the North eastern region of Nigeria are unaccounted for as such these emissions cannot be monitored or controlled. This research estimated GHG emissions into the atmosphere from the current SWM technique practiced in the region, GHG emissions from two different waste management techniques – open burning and incineration was also simulated. The research found that incineration with electricity recovery is the most suitable SWM process therefore suggested that the authorities and other stakeholders in the region should give it serious consideration.